Pueraria lobata starch regulates gut microbiota and alleviates high-fat high-cholesterol diet induced non-alcoholic fatty liver disease in mice. (July 2022) - Yang, Yifei; Li, Mingxing; Wang, Qin; Huang, Huimin; Zhao, Yueshui; Du, Fukuan; Chen, Yu; Shen, Jing; Luo, Haoming; Zhao, Qianyun; Zeng, Jiuping; Li, Wanping; et al.
Graphical abstract: Highlights: A comprehensive analysis of morphology, structure and physiochemical property of Pueraria lobata starch (PLS). In vitro fermentation of PLS promotes growth of Lactobacillus, and increases SCFA production. PLS alleviates dyslipidemia, inflammation and hepatic steatosis in HFD-induced NAFLD in mice. PLS ameliorates NAFLD-associated gut dysbiosis in mice and enhances fecal SCFA level. A potential prebiotic effect of PLS, supporting its use as functional food. Abstract: The dried roots of Pueraria lobata (Willd.) Ohwi as an edible medicinal herb are enriched with starch. However, the structure, physiology, and biological bioactivity of P. lobata starch (PLS) has not yet been fully investigated. This study showed that PLS consisted of mixed population of granules with polyhedral or spherical surface. The apparent content of resistant starch was 23.14%, and the molecular weight was 1.93 × 10 7 Da. PLS showed a branching degree and an average polymerization rate of 2.06% and 20.74%, respectively, with fairly high proportion of B1 short chains. The solubility and swelling power of PLS were 38.51% and 28.10 g/g, respectively, showing high hot stability of the viscosity. In vitro fermentation of PLS resulted in specifically altered composition of gut microbiota and increased production of SCFAs, showing a potential prebiotic effect. Moreover, PLS remarkably alleviated inflammation, hepatic steatosis and dyslipidemia in mice with high-fat high-cholesterol diet induced non-alcoholic fatty liver disease (NAFLD). The protective effect of PLS was associated with amelioration of NAFLD-associated gut dysbiosis through specifically increasing the abundance of Lactobacillus, Bifidobacterium and Turicibacter, and decreasing Desulfovibrio . The results would support the use of PLS as a functional prebiotic for protecting against NAFLD.